Valoración económica del servicio ecosistémico del Parque Nacional Podocarpus, sector Cajanuma, periodo 2022: un enfoque desde el método de valoración contingente - Ordoñez Fierro, Andres Geovanny (2023)
Environmental services set a value around 16 to 54 trillion of dollars annually by ecosystems in the world. The following research determined, through an econometric model, the economic value of the recreational ecosystem service provided by the Podocarpus National Park, an approach based on the contingent valuation method. The data collected was through a survey, which allowed us to know the necessary data for the research and thus determine the willingness to pay for the use and conservation of Podocarpus National Park. The results show that the average age of the respondents is between 25 years; men are the ones who visit the park the most. Regarding the calculated WTP of use, this is $2.43, which is lower than that of conservation, which is $6.15, and we also show that the respondents have greater ecological awareness than recreation, with women being the more concerned about environmental conservation. Based on these results, it is recommended that public policies focused on environmental assessment and conservation, in order not only to depend on the Government but also on external entities, since citizens benefit from the existence of these spaces.